GAME MODEL BASED ON LOCAL WISDOM VALUES AS AN EFFORT TO INCREASE SOCIAL AND GROSS MOTORICABILITIES OF EARLY CHILDHOOD - Hanafiah, .; Gaffar, Andriana; Nurapriani, Reni (PEOPLE: International Journal of Social Sciences, 2017)
This research was conducted in an effort to find an alternative model of the right game for early childhood in West Java region. Factually, rapid technological developments have negatively impacted the development of rough social and motor skills of early childhood. Early childhood is more likely to be passive and less interacting with the environment because it is spoiled by various games that have been supported by virtual technology. Given the diverse Indonesian culture, the researchers tried to develop an interesting game model as well as inculcate the value of local wisdom to the next generation of the nation. The results of this study are expected to stimulate the development of children, improve gross motoric skills, providing alternative activities play in harmony with the values of local wisdom, cultivate children to skillfully move and process the body, motivate teachers to create activities and learning experiences appropriate to the child’s development and situation, introduce and strive to preserve local wisdom in early childhood. Another hope is to provide opportunities for students to improve their motor skills without losing a joyful childhood through playful learning activities, recognizing and trying to preserve the values of local wisdom. This game model is developed through research and development methods with a combination approach. Data and information digging was done in 4 TK / PAUD located in West Java area using observation technique, questionnaire and documentation study. The research findings obtained at the location of research is 1) the implementation of educational programs for young children in the area of West Java is still not optimal; 2) the variety of games for early childhood taught by the teacher has not been colored by efforts to recognize and preserve the value of local wisdom; and 3) the trial results of the children game model based on local wisdom shows a significant increase in early childhood social and motor skills in West Java.